DESIGN OF LINEAR GENERATOR FOR WAVE ENERGY CONVERSION SYSTEM IN MALAYSIA - MOHD ZAMRI, NAILY AKMAL (2019)
Wave energy is one of the available renewable energy resources with vast availability worldwide. The lower wave power density in Malaysia compared to other countries with progressive development in Wave Energy Converter (WEC), leads to the need for a specific direct drive linear generator design that suit the local wave characteristics (i.e. wave height and period).